Fluktuasi Genangan Air dan Pemberian Campuran Kapur dan Kompos Jerami Padi: Pengaruhnya terhadap pH dan Fe Larut pada Tanah Sulfat Masam - Fajar Prayoga; Muhammad Mahbub; Afiah Hayati (Department of Soil, Faculty of Agriculture, Lambung Mangkurat University, 2023)
Swamps in Indonesia are widely spread over four major islands, namely in Sumatra, Kalimantan, Papua, and Sulawesi Papua. The problem with acid-sulfate soils is when the pyrite layer is oxidized. This study used a two-factorial with completly randomized design (CRD). The first factor was flooding fluctuation an the second factor was lime with straw compost. The soil parameters tested were pH and soluble Fe. Observations in the second week of the treatment of fluctuations in puddles that were drained, then flooded and added with a mixture of 3 t ha-1 lime, and 2.5 t ha-1 of straw compos resulted in the highest pH of 6.21. The best soil pH was given lime at 3 t ha-1, both flooded and drained. Observations in the fourth week produced the highest pH, namely 4.80. The pH value of the slightly acidic soil was due to an oxidation-reduction process. The 2nd week of observation had the highest soluble Fe value of 221 mg kg1, which was due to the analysis of soluble Fe using a pH of 4.8 so that Fe2+ increased in dissolved Fe. The fourth week of observation had the lowest soluble Fe value of 56.34 mg kg-1. This was due to flooding and the application of a mixture of lime and rice straw compost. The results of the study show that the interaction of fluctuations in water, lime, and rice straw compost that can affect soil pH and the solubility of soil soluble iron (Fe2+).